2018
DOI: 10.1590/1808-1657000722016
|View full text |Cite
|
Sign up to set email alerts
|

Survival and injuries of Deois flavopicta (Stal., 1854) in pastures under seed treatment with insecticides and dry mass yield

Abstract: The present study evaluated the survival and injuries of Deois flavopicta (Hemiptera: Cercopidae) in pastures of Urochloa (Syn. Brachiaria) decumbens and U. brizantha, submitted to seed treatment with fipronil (Amulet®) and thiamethoxam (Cruiser 350 FS®), and dry mass yield. The experiment, carried out at the APTA Experimental Unity, São José do Rio Preto, SP, Brazil, was designed in randomly blocks, with six treatments (factorial 2x3) and four replications. Sowing was manual, with 12.0 kg ha-1 seeds. Twenty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As for the susceptibility of species to the leafhopper attack, grasses of the Brachiaria genus are preferentially attacked by these insects (BORGHI et al, 2018), as verified by scientific studies, such as the one carried out by Auad et al (2009) and Pereira et al (2018). These studies found a higher leafhopper population density in the Brachiaria brizantha and Brachiaria decumbens species, respectively.…”
Section: Introductionmentioning
confidence: 80%
“…As for the susceptibility of species to the leafhopper attack, grasses of the Brachiaria genus are preferentially attacked by these insects (BORGHI et al, 2018), as verified by scientific studies, such as the one carried out by Auad et al (2009) and Pereira et al (2018). These studies found a higher leafhopper population density in the Brachiaria brizantha and Brachiaria decumbens species, respectively.…”
Section: Introductionmentioning
confidence: 80%
“…The literature is poor reporting efficacy of spittlebug control strategies for forage species. Recently, Pereira et al 43 reported Thiamethoxam as an effective strategy for seed treatment of signal grass to control D. flavopicta.…”
Section: Discussionmentioning
confidence: 99%
“…ex A. Rich Stapf]) [13] Agronomy 2024, 14, 943 2 of 18 monocultivation and high temperatures in the country have led to outbreaks of spittlebugs (Hemiptera: Cercopidae), the main pests in pastures in tropical America [14][15][16][17][18]. Nymphs and adults of this insect pest damage host plants by sucking the sap and injecting toxins that induce phototaxis and reduce photosynthetic rates [19][20][21][22][23], leading to a loss of biomass availability for cattle and reducing the support capacity by 60% on average [15,16,19,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other strategies to address spittlebug attacks on forages in a sustainable manner are being developed. These include the induction of plant resistance to spittlebug attacks [15,21,29], the use of plant compounds as biocontrol agents [30,31], pasture diversification [15], soil fertilization [21,32] and the use of entomopathogenic fungi [17,22,33].…”
Section: Introductionmentioning
confidence: 99%